Comparison of behavioural activation with guided self-help for treatment of depression in adults with intellectual disabilities: a randomised controlled trial. (December 2017) - Jahoda, Andrew; Hastings, Richard; Hatton, Chris; Cooper, Sally-Ann; Dagnan, Dave; Zhang, Ruiqi; McConnachie, Alex; McMeekin, Nicola; Appleton, Kim; Jones, Rob; Scott, Katie; Fulton, Lauren; et al.
Summary: Background: Psychological therapies are first-line interventions for depression, but existing provision is not accessible for many adults with intellectual disabilities. We investigated the clinical and cost-effectiveness of a behavioural activation intervention (BeatIt) for people with intellectual disabilities and depression. BeatIt was compared with a guided self-help intervention (StepUp). Methods: We did a multicentre, single-blind, randomised, controlled trial with follow-up at 4 months and 12 months after randomisation. Participants aged 18 years or older, with mild to moderate intellectual disabilities and clinically significant depression were recruited from health and social care services in the UK. The primary outcome was the Glasgow Depression Scale for people with a Learning Disability (GDS-LD) score at 12 months. Analyses were done on an intention-to-treat basis. This trial is registered with ISCRTN, number ISRCTN09753005. Findings: Between Aug 8, 2013, and Sept 1, 2015, 161 participants were randomly assigned (84 to BeatIt; 77 to StepUp); 141 (88%) participants completed the trial. No group differences were found in the effects of BeatIt and StepUp based on GDS-LD scores at 12 months (12·03 [SD 7·99] GDS-LD points for BeatIt vs 12·43 [SD 7·64] GDS-LD points for StepUp; mean difference 0·26 GDS-LD points [95% CI −2·18 to 2·70]; p=0·833). Within-group improvements in GDS-LD scores occurred in both groups at 12 months (BeatIt, mean change −4·2 GDS-LD points [95% CI −6·0 to −2·4], p<0·0001; StepUp, mean change −4·5 GDS-LD points [–6·2 to −2·7], p<0·0001), with large effect sizes (BeatIt, 0·590 [95% CI 0·337–0·844]; StepUp, 0·627 [0·380–0·873]). BeatIt was not cost-effective when compared with StepUp, although the economic analyses indicated substantial uncertainty. Treatment costs were only approximately 3·6–6·8% of participants' total support costs. No treatment-related or trial-related adverse events were reported. Interpretation: This study is, to our knowledge, the first large randomised controlled trial assessing individual psychological interventions for people with intellectual disabilities and mental health problems. These findings show that there is no evidence that BeatIt is more effective than StepUp; both are active and potentially effective interventions. Funding: National Institute for Health Research.